2020
DOI: 10.1039/c9dt03744f
|View full text |Cite
|
Sign up to set email alerts
|

Relative hemilabilities of H2B(az)2 (az = pyrazolyl, dimethylpyrazolyl, methimazolyl) chelates in the complexes [M(η-C3H5)(CO)2{H2B(az)2}] (M = Mo, W)

Abstract: The question of B–H–Mo hemilability in a range of dihydrobis(azolyl)borate scorpionate ligands is discussed with reference to η3-allyl complexes [Mo(η3-C3H5)(CO)2{H2B(az)2}] [az = pyrazolyl (pz), dimethylpyrazolyl (pz*), mercaptoimidazolyl (mt)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 153 publications
0
4
0
Order By: Relevance
“…In silico Molecular docking studies were carried out by AutoDock software for a synthesized ligand and their Cu(II), Ni(II), and Co(II) complexes with the DNA and two selected proteins (YmaH and ecKAS III). The predicted binding energy and other results are summarized in Tables (3)(4)(5). According to the obtained results of these studies, the investigated receptors showed better interactions with most of the synthesized metal complexes compared to the free ligands.…”
Section: Molecular Docking Analysismentioning
confidence: 87%
See 1 more Smart Citation
“…In silico Molecular docking studies were carried out by AutoDock software for a synthesized ligand and their Cu(II), Ni(II), and Co(II) complexes with the DNA and two selected proteins (YmaH and ecKAS III). The predicted binding energy and other results are summarized in Tables (3)(4)(5). According to the obtained results of these studies, the investigated receptors showed better interactions with most of the synthesized metal complexes compared to the free ligands.…”
Section: Molecular Docking Analysismentioning
confidence: 87%
“…Since the first reportage of poly(pyrazolyl)borates and in especially bis(pyrazolyl)borates by Trofimenko, these compounds have been developed in the inorganic coordination chemistry area and widely employed in various transition metal coordination complexes as anionic Ndonor ligands. [1][2][3][4][5] In these type of the ligands, by controlling the number of pyrazolate rings and the substituents of different derivatives, their structure can be modified for the design and synthesis of the ligands with special properties to formation of stable complexes. [6][7][8] On the other hand, the excellent therapeutic properties of pyrazole-based drugs have attracted the attention of pharmaceutical chemists for the synthesis, development and investigation of various new chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%
“…39 The H 2 B(pz*) 2 ligand also demonstrates a proclivity in group 6 for the adoption of facial tridentate κ 3 - H , N , N ′ chelation. 40 In contrast, the organometallic chemistry of divalent platinum ligated by poly(pyrazolyl)borates often leads to situations where the denticity of the scorpionate is less well-defined. 41 In general for d 6 -organoplatinum( iv ) complexes, tridentate coordination of the Tp* ligand is the norm, however for d 8 -platinum( ii ), the particularly favourable square-planar geometry tends to take precedence, discouraging facial tridentate coordination, be it through 3-centre, 2-electron B–H⋯Pt interaction for the H 2 B(pz*) 2 ligand 42 or κ 3 - N , N ′, N ′′ coordination of all three pyrazolyl donors for tris(pyrazolyl)borates.…”
Section: Resultsmentioning
confidence: 99%
“…Such ligands may be grouped according to their charge (neutral, mono-or di-anionic) which in turn impacts the charge of the derived complexes (cationic, neutral or anionic, respectively). In the case of complexes of the form [W(≡CC 6 H 4 Me-4)(CO) 2 (L)] x+ , a number of these have been compared in terms of the experimentally determined infrared data for the cis-dicarbonyl oscillator [67,[77][78][79][80][81][82][83][84][85][86][87][88][89]. In addition to the frequencies of the observed symmetric and antisymmetric modes (A 1 ν s(CO) , B 1 ν as(CO) ), the two numbers may be condensed into a singular Cotton-Kraihanzel force constant [90].…”
Section: Quantification Of Steric and Electronic Featuresmentioning
confidence: 99%